Development of Problem-Based Learning E-Worksheet to Improve Student Learning Outcomes in Acid-Base Material for Grade XI Senior High School Students Phase F - Herianto; Okta Suryani (Postgraduate, University of Mataram, 2025)
This study aimed to develop a Problem-Based Learning Electronic Student Worksheet to improve learning outcomes in acid-base material for Grade XI students. The research employed a developmental design using the Plomp model, encompassing preliminary investigation, design and prototype development, and assessment phases. Data collection involved expert validation, teacher and student evaluations, and pre-test/post-test assessments with Grade XI students from a public senior high school selected through purposive sampling. The results demonstrated high validity with Aiken's V values of 0.86 for content validity, 0.83 for media validity, and 0.86 for learning validity. Practicality assessment revealed high acceptance with teacher ratings of 4.38 on a five-point scale and 90.46% student acceptance rate. Effectiveness testing showed significant improvement in learning outcomes, with mean scores increasing from 71.61 to 89.44. Statistical analysis using paired sample t-test indicated significant differences with Cohen's d effect size of 2.26, demonstrating substantial educational impact. The study concluded that the Problem-Based Learning Electronic Student Worksheet is valid, practical, and effective for enhancing student learning outcomes in acid-base chemistry, providing a valuable digital learning resource for twenty-first century chemistry education